Propensity-matched analysis of minimally invasive approach versus sternotomy for mitral valve surgery. Issue 10 (12th December 2018) - Grant, Stuart W; Hickey, Graeme L; Modi, Paul; Hunter, Steven; Akowuah, Enoch; Zacharias, Joseph
Abstract : Objective: The objective of this multicentre study was to compare short-term and midterm outcomes between sternotomy and minimally invasive approaches for mitral valve surgery. Methods: Data for all mitral valve procedures with or without concomitant tricuspid atrial fibrillation surgery were analysed from three UK hospitals between January 2008 and December 2016. To account for selection bias between minimally invasive approach and sternotomy, one-to-one propensity score calliper matching without replacement was performed. The main outcome measure was midterm reintervention free survival that was summarised by the Kaplan-Meier estimator and compared between treatment arms using the stratified log-rank test. Results: A total of 2404 procedures (1757 sternotomy and 647 minimally invasive) were performed during the study period. Propensity score matching resulted in 639 matched pairs with improved balance postmatching in all 31 covariates (absolute standardised mean differences <10%). Despite longer procedural times patients who underwent minimally invasive surgery had a lower need for transfusion (20.5%vs14.4%, p=0.005) and reduced median postoperative length of stay (7 vs 6 days, p<0.001). There were no statistically significant differences in the rates of in-hospital mortality or postoperative stroke. Reintervention-free survival at 8 years was estimated as 86.1% in the minimally invasive group and 84.1% in the sternotomy group (p=0.40). Conclusions: Minimally invasive surgery is associated with excellent short-term outcomes and comparable midterm outcomes for patients undergoing mitral valve surgery. A minimally invasive approach should be considered for all patients who require mitral valve intervention and should be the standard against which transcatheter mitral techniques are compared.